Two‐eyed seeing: A useful gaze in Indigenous medical education research. Issue 3 (20th January 2020) - McKivett, Andrea; Hudson, Judith N.; McDermott, Dennis; Paul, David
Abstract: Context: Medical education has a role in preparing future health care practitioners to have the skills to meaningfully address health disparities while providing effective clinical care considerate of diversity in our societies. This calls for medical education researchers to approach their craft in ways that prioritise and value inputs from a broader range of perspectives and worldviews in an effort to redress the negative impacts of social, political and structural forces on health outcomes. Methods: Given the entrenched health inequities experienced by Indigenous populations across the globe, this paper details an approach to medical education research put forward by Canadian Mi'kmaw Elders Murdena and Albert Marshall and named 'two‐eyed seeing'. This approach provides the opportunity for medical education researchers to address the ongoing impacts of colonisation, racism and marginalisation on health outcomes by prioritising Indigenous worldviews in medical curricula. The need for researchers and medical academies to critically consider Indigenous governance and processes of respectful knowledge sharing within the wider institutional and societal contexts is addressed. Conclusions: The benefits of two‐eyed seeing in the context of better preparing the future workforce to effectively meet the needs of those most vulnerable, and to action change against health inequities, situate it as a promising research approach in medical education. Abstract : In this 'research approaches' article, McKivett et al. explore the goal of addressing health disparities and argue for the inclusion and prioritisation of diverse perspectives and ways of knowing.